A study on 65 % potential efficiency of the gas turbine combined cycle - 권현민; 문성원; 김동섭; 강도원; 손정락; 이정호 (Journal of Mechanical Science and Technology, 2019)
This study investigates the possibility of achieving 65 % efficiency in a gas turbine combined cycle. Several options to realize it were compared. A sensitivity analysis was performed for the latest H-class gas turbine in a simple cycle to quickly and easily predict the performance variation due to changes in each design parameter. When each design parameter was improved by the same percentage, the combined cycle efficiency was maximized by the improvement in turbine efficiency. The degree of increase in the combined cycle power was the largest when improving the turbine inlet temperature (TIT). To realize the turbine industry’s goal of 65 % efficiency in the combined cycle, the efficiency of the compressor and the turbine should be improved by 2 %, the TIT should be increased by 100 o C, and the pressure ratio should be increased from 23 to 32 in comparison to current H-class gas turbines. The possibility of improving the cycle performance was also investigated through modifications of the gas turbine cycle, such as reheating, inter-cooling, and recuperation. When reheating and recuperation were adopted simultaneously, a cycle efficiency of 65 % was possible with an increase of 1 % in both the compressor and turbine efficiencies, which is a moderate and practical improvement.
Keywords: Gas turbine; Combined cycle power plant; Sensitivity analysis; Cycle modification; Gas turbine reheating; Recuperation